2016
DOI: 10.3390/w8120587
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Analysis of Egg-Shaped Sewer Pipes Flow Performance

Abstract: A Computational Fluid Dynamics (CFD) model was developed toanalyze the open-channel flow in a new set of egg-shaped pipes for small combined sewer systems. The egg-shaped cross-section was selected after studying several geometries under different flow conditions. Once the egg-shaped cross-section was defined, a real-scale physical model was built and a series of partial-full flow experiments were performed in order to validate the numerical simulations. Furthermore, the numerical velocity distributions were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…The radius of the infundibular zone in typical ovoid forms is equal to half the diameter. -Picallo et al, 2016) We also suggested dividing the forms into sphere-like, roundish, obtuse, typical, drop-shaped and cone-shaped according to the location of the upper edge of the cloacal circle. We can divide these forms into short, short cut, normal, elongated, and long by the size of the lateral arcs.…”
Section: Discussionmentioning
confidence: 99%
“…The radius of the infundibular zone in typical ovoid forms is equal to half the diameter. -Picallo et al, 2016) We also suggested dividing the forms into sphere-like, roundish, obtuse, typical, drop-shaped and cone-shaped according to the location of the upper edge of the cloacal circle. We can divide these forms into short, short cut, normal, elongated, and long by the size of the lateral arcs.…”
Section: Discussionmentioning
confidence: 99%
“…This could imply more risk for reduced capacity of the pipes. On the other hand, there are good examples of very old pipes that due to their shape, e.g., egg-shape section and material construction, have a better function than newer pipes [68].…”
Section: Systemic Inequity Of Flood Exposurementioning
confidence: 99%
“…In recent years, CFD models have been applied for solving several hydraulic engineering problems. In this way, CFD has been used for a variety of purposes, as simulations of flow transient in pipes [19,20], behaviour of different control valves under different conditions [21][22][23][24], mixing models in water distribution systems [25][26][27][28], or for the characterization of elements in open channels [29][30][31][32][33][34].…”
Section: Computational Fluid Dynamics (Cfd) Modellingmentioning
confidence: 99%